Kleen enema Hypophosphatemia correction in hemodialysis patients. - Naveed, Kunwer (Pakistan Journal of Kidney Diseases, 2022)
Dialysis fluid (Dialysate) is a solution consisting of inorganic ions and glucose. Its constitution is almost physiologic. Dialysate is prepared by mixing two concentrates (either liquid or powder form). Two concentrates are labeled as acidic bath (Bath A) and basic bath (Bath B). Bath A contains sodium, chloride and glucose at physiologic concentration. While Bath B is bicarbonate solution contains bicarbonate slightly greater than physiologic concentration to treat metabolic acidosis. Just as therapeutic drugs, Dialysis fluid constituents can be adjusted as per individual patient’s needs. Potassium and calcium baths are available to alter concentration of these ions. Phosphorous is normally not present in dialysate. Though hyperphosphatemia is one of the major clinical problem in renal failure, low serum phosphorous (PO4) is frequently encountered clinical entity. In chronic dialysis patient low PO4 is encountered as component of adynamic bone disease. Likewise, phosphorus dis balance is frequent electrolyte imbalance in critically ill patients with renal injury. Dialysis with low PO4 is always a challenge for nephrologist and intensivist. Case reports are available on treatment of symptomatic hypophsotemia using convention hemodialysis with poshphorous enriched dialysate fluid.